Integration of Islamic Mathematics in Quranic Equation and Universe Creation - Roikhan Mochamad Aziz (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami), 2019)
The research aims to find the consistency in the different phenomenon of mathematic such as quranic triangular numbers and creation of universe. The equation number of the triangular numbers is 72319. And also God equation has the same digital number of 72319 to create the universe. The research data is from the Quran and real factor in universe. The methodology use system approach based on prophecies development and empirical values. The approach of the study is descriptive analysis with comparative advantages. Triangular numbers have group of 319, 913, 616 to form reflexivity equation. Allah math has algorythm of 725 to create the universe as Quran Al-Anbiya 21.30. These 2 (two) method have same digital numbers of 472319 that explained in the Quran Al-Hijr 15.87. Conclusions are both approach has consistency numbers of 472319 or Hahslm equation. This Hahslm equation consist of Islam as the integral parts of Universe guidance Theory (UGT).